Expression and initial characterisation of the Plasmodium falciparum general transcription factors TFIIB and TLP - Bing, Steven (Department of Molecular and Cell Biology, 2016)
Malaria is a leading cause of morbidity and mortality worldwide, and results in approximately 600,000 deaths annually. The life cycle of the parasite is complex, and has several distinct stages of development. The transitions between these stages are brought about through tightly controlled and highly synchronized changes in gene expression. Plasmodium falciparum causes the most lethal form of malaria in humans. The parasite is particularly virulent as it is able to evade immune detection by the infected host. This virulence is directly related to the expression of variable antigens on the surface of infected red blood cells. The control of gene expression is known to be largely regulated via RNA Polymerase II (RNAPII) transcription initiation, but in P. falciparum the underlying mechanisms have not been determined. This primarily because very little is known about both the key protein factors and DNA elements which guide the assembly of RNAPII components into the transcription initiation complex. Bioinformatics studies have shown that there is very little amino acid sequence conservation between human and Plasmodium RNAPII transcription initiation components. Together with the observation that the Plasmodium genome has an extremely high A+T content, this suggests that Plasmodium may have specific mechanisms to initiate transcription, which could be targeted by novel anti-malarials. The general transcription factor TFIIB and the TBP-like protein (TLP) are key proteins involved in the recognition of the core promoter, and the initiation of RNAPII transcription initiation complex assembly. TFIIB stabilises DNA binding of the primary promoter recognition factor, TATA-box binding protein (TBP), and is involved in promoter recognition through interactions with specific DNA sequences up- and downstream of the TBP DNA binding site. TBP-like protein is a member of the TBP protein family that has been implicated in life cycle stage specific gene transcription initiation in various eukaryotic model organisms. This research study reports the first successful expression and purification of recombinant epitope-tagged Plasmodium falciparum TFIIB and TLP proteins. Preliminary assays demonstrate DNA-binding activity for the recombinant Plasmodium TBP-like protein, and suggest DNA-binding activity in Plasmodium TFIIB protein, which has not been demonstrated before in eukaryotic TFIIB.